Dementia awareness and risk perception in middle-aged and older individuals: baseline results of the MijnBreincoach survey on the association between lifestyle and brain health - Irene Heger; Kay Deckers; Martin van Boxtel; Marjolein de Vugt; KlaasJan Hajema; Frans Verhey; Sebastian Köhler (BMC, 2019)
Abstract Background The total number of people with dementia is increasing worldwide, due to our aging society. Without a disease-modifying drug available, risk reduction strategies are to date the only promising way to reduce dementia incidence in the future. Substantial evidence exists that lifestyle factors contribute to the risk of dementia, such as physical exercise, mental activity and (non-)smoking. Still, most people seem unaware of a relationship between lifestyle and brain health. This paper investigates dementia literacy and knowledge of modifiable risk and protective factors of dementia in a Dutch population-based sample. Methods An online-survey was carried out among 590 community-dwelling people between 40 and 75 years old in the Province of Limburg, the Netherlands. The total group comprises both of a provincial sample (n = 381) and a sample of three specific districts within the province (n = 209). Dementia awareness and knowledge about 12 risk and protective factors was assessed with items derived from the British Social Attitudes (BSA) survey, supplemented with custom items developed by the research team. Results The majority of participants (56%) were unaware of a relationship between lifestyle and dementia risk. Most individuals identified low cognitive activity, physical inactivity and unhealthy diet as dementia risk factors. Particular gaps in knowledge existed with regard to major cardiovascular risk factors such as hypertension, hypercholesterolemia and coronary heart disease. Although the level of awareness varied by age and level of education, most people (70%) were eager to learn more about the topic of brain health, and indicated to be interested in using eHealth (54%) to measure or improve brain health. Conclusions Most people still are unaware of the relation between lifestyle and brain health, indicating the need for public health campaigns. Increasing awareness in the general population about the presence of modifiable dementia risk and protective factors is a crucial first step prior to implementation of preventative measures. Targeting specific subgroups, such as individuals with low socioeconomic status and low health literacy, is essential for the reach and effect of a prevention campaign. Outcome of this study was the rationale for an awareness campaign in The Netherlands, called "MijnBreincoach" ("MyBraincoach").